2016
DOI: 10.4172/2155-9554.1000352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Invasive Squamous Cell Carcinoma, Seborrheic Keratosis and Verruca Vulgaris in Superficial Shave Biopsies using p16, p53, p63, and PHLDA1 Immunohistochemistry

Abstract: Occasionally, the distinction between malignant and benign is challenging in superficial shave biopsies of squamoproliferative lesions. This phenomenon is compounded by the increasing prevalence of conditions encountered that weaken the immune system, such as chemotherapy, immune deficiency diseases, and antirejection medications for organ transplantation that have all been shown to increase the risk of the development of squamous cell carcinoma. We collected 30 cases (10 invasive SCC, 10 SK and 10 VV) and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…In our study, 13.3% of SK cases were negative with p16. Other studies found this percentage to be between 35% and 83%, in which the most common patterns were scattered patches of positive cells 9,13‐15 . One study has shown a connection between the intensity of p16 expression and the number of a patient's SK lesions 16 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our study, 13.3% of SK cases were negative with p16. Other studies found this percentage to be between 35% and 83%, in which the most common patterns were scattered patches of positive cells 9,13‐15 . One study has shown a connection between the intensity of p16 expression and the number of a patient's SK lesions 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Delta Np63 is the most common isoform that is normally expressed in the nuclei of epidermal keratinocytes, hair follicle external root sheaths, and hair matrix germinative cells. 8,9 With increasing cell maturation, expression of delta Np63 is reduced. 10 p16INK4a is a product of the cyclin-dependent kinase inhibitor 2A gene (CDKN2A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Brown reported that of 10 seborrheic keratosis samples evaluated for p53 with immunohistochemistry examination, 6 samples (60%) were positive (+), and 4 samples (40%) were positive (++). 22 Another study by Ko reported that of 10 evaluated seborrheic keratoses, the mean value of p53 protein expression was 2.1. This study grouped the value of p53 into 3 sections, 1 if p53 was found in less than 10% cells, 2 if p53 was found between 10%-30% cells, and 3 if p53 was found in more than 30% cells.…”
Section: Table 4 the Correlation Between Hpv And Increased P53 Protmentioning
confidence: 98%
“…In this study, the p53 protein expression was positive in all seborrheic keratosis lesions and some even exhibit an increase in p53 expression. 22 In the pathogenesis of skin malignancy, HPV plays its part in the early phases of malignancy and acts as a co-carcinogen with ultraviolet (UV) rays by aggravating DNA damage. Thus, HPV is abundantly found in pre-malignant lesions as well as benign skin tumors.…”
Section: Table 4 the Correlation Between Hpv And Increased P53 Protmentioning
confidence: 99%